Gambaran Asuhan Keperawatan Pada Pasien Anak Yang Mengalami Hipertermia dengan Dengue Haemorrhagic Fever di RSUD Pasar Rebo Jakarta - Mochamad Robby Fajar Cahya; Indah Fitriyani (Jurnal Persada Husada Indonesia, 2023)
Dengue Hemorrhagic Fever is an infectious disease caused by dengue virus infection which is transmitted through the bite of the Aedes Aegypti mosquito and is characterized by symptoms of fever, muscle pain, joint pain, leukopenia, headache, thrombocytopenia and is usually accompanied by bleeding spots (petechiae). The purpose of this study was to determine the description of nursing care for child clients and families who have the same characteristic as male sex, and school age, and have the main problem of hyperthermia with a medical diagnosis of Dengue Hemorrhagic Fever. The research design used is descriptive qualitative with a case study and intervention approach. After conducting a nursing assessment on Children found complaints of fever, dizziness, and weakness. Found 3 diagnoses in the client, where the priority diagnosis is the nursing diagnosis of Hyperthermia related to the disease process. One of the independent actions taken is giving warm compresses with a frequency of 1x a day for 10-15 minutes. At the evaluation stage of the three nursing diagnoses owned by the client, it was carried out according to the planning, and the final evaluation obtained was resolved according to the criteria of 3 x 24 hours. Giving a warm compress that has been done by the author turned out to be effective in helping to overcome the problem of hyperthermia with the result that body temperature decreases. Based on the results of the research that has been carried out, the authors give suggestions to nurses to further improve independent actions in helping to overcome hyperthermia in pediatric clients with Dengue Hemorrhagic Fever.